Bimaxillary orthognathic surgery with a conventional saw compared with the piezoelectric technique: a longitudinal clinical study. Issue 8 (October 2018) - Rossi, D.; Romano, M.; Karanxha, L.; Baserga, C.; Russillo, A.; Taschieri, S.; Del Fabbro, M.; Giannì, A.B.; Baj, A.
Abstract: The only cutting technique used for osteotomies in orthognathic surgery for many years has been a saw, but recently piezoelectric surgery has been introduced as a possible alternative. The aim of this study was to find out if piezoelectric surgery can be more comfortable for patients having orthognathic surgery. A total of 25 patients with dentofacial deformities (seven male and 18 female), were treated from January 2016 to September 2017. In 11 patients, osteotomies were made using a conventional saw, while in 14 a piezoelectric device was used. The variables assessed were: operating time, postoperative swelling, postoperative pain, and cutaneous sensitivity of the upper and lower lips. The duration of operation for the piezosurgery group was significantly longer than that for controls, but the patients had less swelling at all follow-up visits, and the difference was significant at the 30-day follow-up (p = 0.045). Those who had piezosurgery had significantly less pain at the three-day follow up (p = 0.035). There was a significant difference in cutaneous sensitivity only for the right side of the upper lip and only at the one-day follow-up. We conclude that piezoelectric surgery offers some advantages in lessening swelling and the perception of pain after orthognathic surgery, but further investigations are required.